UGANDANS INTENTION TO BUY FORD RANGE RAPTOR DURING THE CORONA VIRUSES PANDEMIC 2020 - Mujuni Kenneth Nyakairu; Cahyani Pratisti (Prosiding International conference on Information Technology and Business (ICITB), 2020)
The Corona Viruses Pandemic affected Uganda’s vehicle market that losing 34.4% compared to last year but Ford cars by Cooper Motor Co-operation have continued to raise with 5% increase per year. The purpose of this study was to describe how Ugandans intention to buy a Ford Ranger Rover during the corona viruses perdemic. The type of study used descriptive qualitative study with 30 questionnaires. It was analyzed by descriptive analysis found that 60% interested to buy and 25% maybe buy this car because of the cars durability, off-road capability, and the fuel consumption it stated that it was so economic friendly. Over 25% of the people had highlighted that the car was too expensive for them since most Ugandans were middle wage earners. Thus this paper suggested that Ford Company together with its franchise holder in Uganda CMC had to reduce the prices for this 2020 Ford Range Raptor to a favorable price for these 25% people.Keyword: Corona Viruses Pandemic, Intention to buy, Car